Competencies and Interactions in Design Management - Cláudia de Souza Libânio; Fernando Gonçalves Amaral (BBR: Brazilian Business Review)
The inclusion of design in corporate strategies has been a recurring research theme, and organizations are using it as strategic element for gaining competitive advantage in the long term. Thus, it becomes evident the need to manage design activities, making use of concepts related to competencies, learning, dynamic capabilities and other aspects. Therefore, this paper aims at investigating what experts think about design management and competencies, joints and intervenient factors in Brazilian fashion industry. In addition, this ar ticle aimed at knowing how design teams are structured and the relationship of these with the organization. The methodology was exploratory, qualitative, through in - depth interviews with ten designers working in Brazilian firms in the fashion industry and four specialists in fashion design. We identify phases and activities of design professional, which are decisive for the design management occurrence in enterprises in apparel industry, identifying the coworkers at each stage of this process.